2021
DOI: 10.3390/ijms22073739
|View full text |Cite
|
Sign up to set email alerts
|

Radiation on Earth or in Space: What Does It Change?

Abstract: After having been an instrument of the Cold War, space exploration has become a major technological, scientific and societal challenge for a number of countries. With new projects to return to the Moon and go to Mars, radiobiologists have been called upon to better assess the risks linked to exposure to radiation emitted from space (IRS), one of the major hazards for astronauts. To this aim, a major task is to identify the specificities of the different sources of IRS that concern astronauts. By considering th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 96 publications
0
19
0
2
Order By: Relevance
“…Only during the Apollo missions, conducted by the United States of America in the late 1960s and early 1970s have humans left the LEO. In the LEO, the Earth’s magnetic field shields away most of the radiation coming from space, especially radiation types with higher energies [ 81 ]. Thus, radiation effects on the joint cartilage of spaceflight participants can be expected to be more pronounced on deep-space missions beyond the LEO, such as to the Moon and Mars, compared with findings obtained in crew staying on space stations that orbit Earth.…”
Section: Findings From Spaceflightmentioning
confidence: 99%
“…Only during the Apollo missions, conducted by the United States of America in the late 1960s and early 1970s have humans left the LEO. In the LEO, the Earth’s magnetic field shields away most of the radiation coming from space, especially radiation types with higher energies [ 81 ]. Thus, radiation effects on the joint cartilage of spaceflight participants can be expected to be more pronounced on deep-space missions beyond the LEO, such as to the Moon and Mars, compared with findings obtained in crew staying on space stations that orbit Earth.…”
Section: Findings From Spaceflightmentioning
confidence: 99%
“…Another source of radiation is the interaction of solar and CGR with shielding, creating high Linear Energy Transfer (LET) but low energy metallic particles and protons. The inside of the vessel is also subjected to a higher constant low dose of gamma radiation, about twice the highest natural radiation background found on Earth (Restier-Verlet et al, 2021).…”
Section: The Effect Of Radiation On the Cardiovascular Systemmentioning
confidence: 99%
“…The radiation doses received for space explorers depend on the time and distance from earth. Estimated doses are 150 mSv/year for space flight in the ISS, 300-400 mSv for traveling to the Moon, and 300-400 mSv/year and 1600-2300 mSv for 2 years traveling to Mars (Shavers et al, 2004;Chancellor et al, 2018;Restier-Verlet et al, 2021) in higher doses of radiation (>100 mGy) it has been clinically shown to lead to cardiac dysfunction over time, where cases have been reported following radiotherapy. Short and longterm effects of radiation induced cardiovascular diseases were observed following radiotherapy treatment of cancers adjacent to heart including lungs, breasts, and esophagus.…”
Section: The Effect Of Radiation On the Cardiovascular Systemmentioning
confidence: 99%
“…De plus, le lien entre radiosensibilité et certaines mutations génétiques reste encore méconnu (Foray et al, 2016). dans le cadre de l'exploration spatiale : l'exploration spatiale requiert une meilleure connaissance des effets biologiques des radiations cosmiques : ce domaine inclut les effets spécifiques aux particules lourdes, aux faibles doses et aux faibles débits de doses (Restier-Verlet et al, 2021). en environnement : avec l'identification des effets spécifiques imputables aux radionucléides dispersés dans l'environnement, la radiobiologie devient également environnementale avec des interactions nombreuses avec les géologues, les botanistes, les experts des différents écosystèmes biologiques.…”
Section: Contexte Généralunclassified